Strain effect on electrical resistivity of thermoexpanded graphite/polyvinylchloride plastisol composite - Karaman, D.Yu.; Kopan, V.S.; Revo, S.L. (Functional Materials, 2005)
The mechanical properties and electrical resistivity of a composite material consisting of polyvinylchloride plastisol material matrix and thermoexpanded graphite filler has been investigated. The percolation threshold has been determined to be θс = 0.04 vol. parts graphite. During the material tension, its specific electrical resistivity р increases linearly in the filler concentration range 0.04 < 0 < 0.60. А model has been proposed for the processes characterizing the system conductivity, which is based on the peculiarities of intergrain contacts in the composite material. Guidelines are given on possible usage of the new obtained material in strain gauges suitable for service at increased humidity and in corrosive media.